PECULIARITIES OF THE WATER PERMEABILITY PROPERTIES OF THE SOIL - Sadullaev , Azamat Nafiddinovich (Educational Research in Universal Sciences, 2024)
This scientific article critically examines the scientific interpretation of soil water permeability properties, providing a thorough analysis of the factors influencing water movement within the soil matrix. Employing advanced experimental techniques and theoretical models, the study delves into the complex interplay of soil structure, particle size distribution, and environmental factors that govern permeability. By elucidating the mechanisms underlying soil water movement, the research enhances our understanding of how soil properties impact hydrological processes, with implications for agriculture, environmental science, and geotechnical engineering. The article aims to contribute to the development of more accurate predictive models and sustainable soil management practices.